2016
DOI: 10.2116/analsci.32.1059
|View full text |Cite
|
Sign up to set email alerts
|

Time-Profile Measurement of an Emulsion Using Multiphoton Ionization Time-of-Flight Mass Spectrometry in Combination with a Microscope

Abstract: Multiphoton ionization time-of-flight mass spectrometry was applied to the measurement of an oil-in-water emulsion that contained toluene as a dispersed phase. Before the measurement, the sample was sufficiently creamed, and then stirred for a short period of time for dispersion. As a result, several intense spikes appeared on the time profile constructed from the peak area for toluene. In the present study, an optical microscope was used to observe the capillary column for sample introduction, and small tolue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(42 citation statements)
references
References 41 publications
6
34
2
Order By: Relevance
“…3 μm in the case of a toluene O/W emulsion. 17 With this technique, we demonstrated the possibility of evaluating the creaming of emulsions from the time course of a peak area. 15 In the present study, we demonstrated the possibility of a quantitative analysis of an oil component in an emulsion via MPI-TOFM, which has not been achieved.…”
Section: 27mentioning
confidence: 99%
See 2 more Smart Citations
“…3 μm in the case of a toluene O/W emulsion. 17 With this technique, we demonstrated the possibility of evaluating the creaming of emulsions from the time course of a peak area. 15 In the present study, we demonstrated the possibility of a quantitative analysis of an oil component in an emulsion via MPI-TOFM, which has not been achieved.…”
Section: 27mentioning
confidence: 99%
“…3 μm could be detected as a spike in the case of a toluene O/W emulsion. 17 By carefully checking the time profiles for styrene, the signal intensity seemed to have decreased sometimes before the occurrence of the intense spikes when measuring emulsions with higher concentrations of styrene. One possible reason is the generation of aggregates of styrene droplets.…”
Section: Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 These spikes indicate the existence of a highly concentrated oil component, which amounts to only a small oil droplet. 19 We also applied this method to the direct measurement of analytes in a water-in-oilin-water (W/O/W) multiple emulsion. 20 LI-TOFMS can produce information about the local microenvironment of an emulsion, and, therefore, we theorized that this technique could be applied to the direct detection of monomers and oligomers generated during emulsion polymerization, which is a polymerization technique.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we also applied LI-TOFMS to the measurement of liquid samples, 34,35 including emulsions. [36][37][38][39] In the present study, we treated TiO2 nanoparticles with PTES and prepared slurry samples where PTES either remained or was removed by washing. Then, a direct mass analysis of the slurries was performed by LI-TOFMS, and we confirmed whether the remaining PTES could be detected.…”
Section: Introductionmentioning
confidence: 99%